PENGALAMAN PEMBENTUKAN KONSEP DIRI PENGGEMAR DALAM MENGIKUTI KEGIATAN "IDOL YOU CAN MEET" DI THEATER JKT48 JAKARTA - Siti Ntara Muthmainah Mulya; Irmulan Sati Tomohardjo (Jurnal Visi Komunikasi, 2021)
The formation of the concept of self is also owned by JKT48 fans. The formation of the concept of the self is influenced by the experience carried out by fans in doing "Idol You Can Meet" at Theater JKT48 Jakarta, interaction between fans and member, interact with fellow JKT48 fans, join to a community that is associated with JKT48. The method used in this research is qualitative - phenomenology. Primary data collection in this reseach is in-depth interview techniques, observation and documentation. The results of the research are explained the experiences endured by fans, The formation of the concept of self in fans after following the activities of "Idol You Can Meet" JKT48, the interaction between fans, and the experiences about socializing among fans in a community.Conclusion of this research is fans can form the self-concept about their self being fans without opening up their I dentity as fans by directly in their environment that are not closest, fans can get many experiences about memorable experiences and disappointing experiences after during following the activities of "Idol You Can Meet" JKT48, the positive influence of member to fans for doing good activities, and fans can socialize with other fans, make a new friend with another fans and join or make community for socialize and support JKT48 together.